STRIVING FOR SUPERIORITY OF KEVIN TIERNEY REFLECTED IN NICHOLAS SPARKS ‘SAFE HAVEN’ NOVEL: THE FORMS AND THE FACTORS - Leander, Phebe Olivia; Lestari, Indah (Journal of Language and Literature, 2021)
The objectives of this research were to find out the forms and the factors of striving for superiority in Kevin Tierney reflected in Safe Haven novel uses a theory striving for superiority from Alfred Adler. Basically, striving for superiority are some people who strive for personal superiority over others to reach perfection in their life, Adler has two forms of striving for superiority, they are the final goal and the striving force as compensation. Furthermore, Adler has three factors of striving for superiority, they are the ceaselessness, adaptation and perfection in abnormal. On the other side, the writer also used qualitative method although obtaining the data. As the result the researcher find out four data of the final goal on the forms of striving for superiority and for the factors of striving for superiority, the researcher found out five data of the ceaselessness, three data of the adaptation, and one data of perfection in abnormal.